Raca žličarica Anas clypeata - Rubinič, Borut (Acrocephalus, 1994)
Female with six chicks on 17th June 1993 at Lake Cerknica
Keywords: Anas clypeata; Birds; Cerkniško jezero; Lake Cerknica; Ornithology; ornitologija; ptiči; raca žličarica; Retje; Slovenia; Slovenija